The Last Mile in Ending Extreme Poverty : A Memoir of International Peacekeeping in the 21st Century - Kharas, Homi J., 1954-; Katō, Hiroshi, 1926-2013; Chandy, Laurence (Book collections on Project MUSE., 2015)
"Examines through new evidence, ideas, and solutions how to implement three central changes that could lead to the eradication of extreme poverty in the world: breaking cycles of conflict, supporting inclusive growth, and managing shocks and risks"--